O Facebook como recurso pedagógico para o ensino de biologia - Vieira, Walas Cazassa (2017)
The purpose of this work to use the social network Facebook as a pedagogical resource directed to biology classes in the high school and evaluate the use of groups in the social network as auxiliary teaching tools of the discipline. In this way, we sought to use groups created in this social network for work content during school, sharing with students several materials, in order to illustrate different forms the topics discussed, besides providing them some materials extras related to discipline. With that, we tried to take advantage as much as possible of the resources presents in the groups created, seeking to enter the student in the proposed activities in groups. Through this study, also noted how this tool can be used on the pedagogical teaching and learning process, taking into account the technological appropriation of such tool. The survey was conducted from the creation of two groups on the social network site by the researcher, that acts a biology teacher in high school, using these to work with two of his classes. Observations were made while working with the groups and application of questionnaires to the students to compose the instruments of data collections. Such questionnaires were used to obtain knowledge about the profile of Internet users students, social networks and the Digital Technologies and for evaluation by students about the use of groups during the school year. During the data collection and analysis, some aspects were observed, among them the little activity of students in groups created and some barriers found by the searcher for use of the methodology in question. At the end of the study, there was the development of an e-book as educational product, where you can find a tutorial for use of Facebook as a pedagogical resource for teaching biology. It was also concluded that digital technologies of information and communication alone are not sufficient to revolutionize the teaching and learning process, demanding a teaching practice that seeks to build student knowledge in a participatory manner, placing it as the protagonist of this process and using such resources as a way to complement and assist in daily practice.